Visualisasi Sejarah dan Sejarah Publik - Patra, Haldi (Jurnal Sejarah, 2020)
Public History's approach is to communicate history audience outside the academic field. the increase of YouTube users has opened the possibility for public historians to creates and upload their historical audio-visual works on their YouTube's channels. This study reviews those channels. There are four channels in this article: Armchair Historian, Oversimplified, Inspect History dan Lazardi Wong Jogya. Every channel has its unique which is offered to viewers. These four channels also success to attract a million viewers to watch its contents. However public historian who focuses on this field can choose this field as their economic valuable career